Pêche, conservation environnementale et aire protégée - Sabrina Doyon; Pierre-Alexandre Paquet (Revue d'ethnoécologie)
In Mexico, the variety of activities and concerns that are currently being deployed along the coasts is growing. In addition to the traditional fisheries coastal fisheries, mass tourism, ecotourism and environmental conservation are now part of the landscape and actively reshaping it. As similar developments also impact the coasts of Yucatán, this article examines the stakes, given the recent transformations affecting this region. Through a critical and diachronic perspective, this article explores the socio-environmental relationships at work in a village located within the Ría Lagartos Biosphere Reserve as well as the processes that are socially and economically marginalizing its inhabitants, and more particularly the local fishermen whose livelihoods are closely tied to the coastal areas now enclaved within the protected area. Based on ethnographic research and a political ecology framework, this article analyzes sea and land uses along the coasts of Las Coloradas. This article also highlights the role of various economic activities – including fisheries, the salt industry, tourism, and environmental conservation – in shaping ongoing negotiations and disputes about coastal and land uses in this region.